FACTORS INHIBITING MEDIATION AND THE IMPACT OF NON-IMPLEMENTATION OF MEDIATORS’ RECOMMENDATIONS IN RESOLVING INDUSTRIAL RELATIONS DISPUTES - Rahmania Puspita (Proceeding International Conference on Social Sciences, 2026)
Mediation serves as a peaceful mechanism used by workers and employers when bipartite negotiations fail to produce agreement. Its core purpose is to reconcile disputing parties through the involvement of a neutral mediator who acts impartially to help achieve fair and balanced outcomes. Mediators authorized to assist in industrial relations disputes operate within official labor institutions, including the Riau Provincial Manpower and Transmigration Office. This study seeks to identify the inhibiting factors that hinder the effectiveness of mediation in resolving industrial relations disputes handled by the Riau Provincial Manpower and Transmigration Office, as well as to analyze the consequences that arise when mediator recommendations are not implemented by workers or employers. The research applies a sociological legal approach, characterized by direct observation and data collection through interviews at designated research locations. This approach enables the study to present descriptive findings that provide a clear and structured understanding of the central issues affecting the mediation process. The findings indicate that the primary obstacle in resolving disputes through mediation lies in the weak cooperation between workers and employers. High levels of ego and unwillingness to compromise from both sides impede the creation of mutually acceptable solutions, resulting in unsatisfactory mediation services. Furthermore, the failure to act upon mediator recommendations specifically those issued by the Riau Provincial Manpower and Transmigration Office leads to prolonged disputes between the parties. Such unresolved disagreements often escalate to the industrial court, which ultimately requires additional time, greater financial resources, and extended conflict for both workers and employers